2018
DOI: 10.1016/j.bbamem.2017.04.024
|View full text |Cite
|
Sign up to set email alerts
|

Human diseases associated with connexin mutations

Abstract: Gap junctions and hemichannels comprised of connexins impact many cellular processes. Significant advances in our understanding of the functional role of these channels have been made by the identification of a host of genetic diseases caused by connexin mutations. Prominent features of connexin disorders are the inability of other connexins expressed in the same cell type to compensate for the mutated one, and the ability of connexin mutants to dominantly influence the activity of other wild-type connexins. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
132
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(133 citation statements)
references
References 165 publications
(162 reference statements)
1
132
0
Order By: Relevance
“…In all cases these results have been derived from visual inspection and using an inclusive criterion. Also, in Table 2 we associate our findings with the recently reported [11, 12] functional state of Cx26 hemichannels, gap-junctions and pathological phenotypes [64]. It is important to notice that due to the three-dimensional approach used here to identify the possible associations between reported mutations and calcium-biding sites from the MD simulations, some mutations are at a distant region of the sequence from that where we find calcium binding sites.…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…In all cases these results have been derived from visual inspection and using an inclusive criterion. Also, in Table 2 we associate our findings with the recently reported [11, 12] functional state of Cx26 hemichannels, gap-junctions and pathological phenotypes [64]. It is important to notice that due to the three-dimensional approach used here to identify the possible associations between reported mutations and calcium-biding sites from the MD simulations, some mutations are at a distant region of the sequence from that where we find calcium binding sites.…”
Section: Resultssupporting
confidence: 72%
“…GLU120 and ASP159. Moreover, a number of calcium binding sites are one or two residues apart from a reported mutation site [11, 12, 15, 6264]. While these observations are important, it is also relevant to take into account the three-dimensional nature of our problem.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most well-known deafness condition associated with impaired ER stress is caused by mutations in genes encoding WFS1 and connexins [57][58][59]. Recently, it was shown that impaired ER stress is also involved in Usher (USH) syndrome [60,61].…”
Section: Er Stress and Hereditary Hearing Lossmentioning
confidence: 99%
“…In vertebrates, gap junction proteins known as connexins are encoded by nearly 20 genes [82]. Mutations in connexin genes have been shown to associate with various types of disease, including peripheral neuropathy, skin disease, cataracts, and hearing loss [59]. Mutations in GJB2, which encodes for connexin 26 (Cx26), contribute tõ 50% of autosomal recessive nonsyndromic hearing loss [83][84][85][86][87][88].…”
Section: Connexins and Er Stressmentioning
confidence: 99%